Biofilm formation of Pseudomonas spp. at the air-liquid interface, EPS matrix composition and resistance to CIP cleaning : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Food Technology at Massey University, Palmerston North, New Zealand - Muthuraman, Srinithi (Massey University, 2026)
Pseudomonads are known for their spoilage potential due to the production of thermostable enzymes and pigments. Pseudomonads can affect a wide range of processing environments, including dairy, poultry, meat, fish, and vegetable processing. The proteolytic, lipolytic and pectolytic enzyme production associated with pseudomonads was witnessed in the past. The high persistence of pseudomonads is observed due to their biofilm formation on food contact surfaces, especially under cold temperatures (e.g. 4°C) and at the air-liquid interface and submerged conditions. Despite the incidences reported of pseudomonad spoilage, limited information exists on their biofilm formation at cold temperatures, matrix compositional differences on food contact surfaces, and how the biofilm formation at cold temperatures affects the cleaning processes. This thesis addresses these research gaps by studying the biofilm formation and matrix composition of pseudomonads at cold temperatures and their control strategies. Among the eleven isolates studied, two isolates, P. lundensis and P. cedrina were identified as strong biofilm formers at cold temperatures with higher biomass and cell counts. This study identified that these two isolates are cellulose-only producers and can form strong biofilms in the absence of curli fibres. The characterization of the extracellular polymeric substances EPS composition revealed that the cold temperatures encouraged increased matrix production with polysaccharides, proteins, and extracellular DNA, which resulted in complex biofilm architecture. The cell-to-EPS ratio was much higher in the biofilms formed on stainless-steel surfaces compared with those on polystyrene surfaces, explaining the influence of temperature and surface type on the biofilm formation of these isolates. The air-liquid interface promoted higher EPS production, as confirmed by the overexpression of EPS-encoding genes in air-liquid interface biofilm cells compared to their submerged counterparts. These findings demonstrate the air-liquid interface as a favourable niche in the biofilm formation of pseudomonads. The cleaning simulation with traditional CIP revealed the EPS footprints left on the stainless-steel surface. The potential of these footprints during recolonisation was shown in both strong and weak biofilm formers. The removal of these footprints using commercial enzyme cleaners resulted in less aggressive biofilm formation during recolonisation. Overall, this thesis addresses the critical research gaps in the biofilm formation of psychrotrophic pseudomonads under cold temperatures. Linking the EPS composition, biofilm architecture and at the different surfaces and interfaces provides practical insights improving cleaning and sanitation and finally reduces the spoilage incidents of these pseudomonad isolates.
Keywords: Pseudomonas; Molecular aspects; Extracellular polymeric substances; Biofilms; Cleaning; Molecular microbiology; 300607 Food technology; 310701 Bacteriology